Польские фамилии в прозе Антона Чехова - Szubin, Roman (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The author considers Polish surnames in Chehov‘s prose from two basic positions – formal and semantic. A Polish surname in Chehov always appears in an intense semantic context and involves ambivalent meanings. Nearly all Polish characters of his works are administrators, managers, or beautiful women. An important point is that a Polish surname in Chehov, regardless of the real national identity of its bearer, starts to function as a sign. Within this aspect, deep semantic structures of the text are involved. According to the author of the article, an adaptation of a foreign surname within the text to be received by the Russian linguistic consciousness is generally effected through an anagram and identification to sound structure of the text.